Comparative Analysis of Azo Dye Biodegradation by Aspergillus oryzae and Phanerochaete chrysosporium - Santos, Graziely Cristina [UNESP]; Corso, Carlos Renato [UNESP] (Springer, 2014)
The textile industry often releases effluents into the environment without proper treatment or complete dye removal. Azo dyes, which are characterized by azo groups (-N=N-), are frequently used in the textile industry. Among the different wastewater treatment methods available, biological treatment has been extensively studied. The aim of the present study was to compare the biodegradation of the azo dye Direct Blue 71 by the fungi Phanerochaete chrysosporium and Aspergillus oryzae in paramorphogenic form using a 100 mu g/ml dye solution. Biodegradation tests were performed within 240 h. The absorbance values obtained with UV-VIS spectrophotometry were used to determine the absorbance ratio and the percentage of dye discoloration following the biodegradation test. FTIR analysis allowed the identification of molecular compounds in the solution before and after biodegradation. Both A. oryzae and P. chrysosporium demonstrated considerable potential regarding the biodegradation of dyes in wastewater. These results may contribute toward improving effluent treatment systems in the textile industry.
Keywords: Direct Blue 71; Fungi; Amines; Paramorphogenic form; UV-VIS; FTIR